Impact of Continuous Quality Improvement Initiatives on Clinical Outcomes in Peritoneal Dialysis. Issue 2 (June 2014) - Yu, Yusheng; Zhou, Yan; Wang, Han; Zhou, Tingting; Li, Qing; Li, Taoyu; Wu, Yan; Liu, Zhihong
Objective: We evaluated the role of a quality improvement initiative in improving clinical outcomes in peritoneal dialysis (PD). Methods: In a retrospective analysis of 6 years of data from a hospital registry, the period between 1 July 2005 and 30 June 2008 (control group) provided baseline data from before implementation of systemic outcomes monitoring, and the period between 1 July 2008 and 30 June 2011 [continuous quality improvement (CQI) group] represented the time when a CQI program was in place. Peritonitis incidence, patient and technique survival, cardiovascular status, causes of death, and drop-out were compared between the groups. Results: In the 370 patients of the CQI group and the 249 patients of the control group, the predominant underlying kidney diseases were chronic glomerulonephritis and diabetic nephropathy. After implementation of the CQI initiative, the peritonitis rate declined to 1 episode in 77.25 patient–months from 1 episode in 22.86 patient–months. Ultrasound parameters of cardiac structure were generally unchanged in the CQI group, but significant increases in cardiothoracic ratio and interventricular septal thickness were observed in the control group (both p < 0.05). Patient survival at 1, 2, and 3 years was significantly higher in the CQI group (97.3%, 96.3%, and 96.3% respectively) than in the control group (92.6%, 82.4%, and 67.3% respectively, p < 0.001). Implementation of the CQI initiative also appeared to significantly improve technique survival rates: 95.6%, 92.6%, and 92.6% in the CQI group compared with 89.6%, 79.2%, and 76.8% in the control group ( p < 0.001) after 1, 2, and 3 years respectively. Conclusion: Integration of a CQI process into a PD program can significantly improve the quality of therapy and its outcomes.